Hearing preservation cochlear implantation in children: The HEARRING Group consensus and practice guide. (2nd January 2018) - Rajan, Gunesh; Tavora-Vieira, Dayse; Baumgartner, Wolf-Dieter; Godey, Benoit; Müller, Joachim; O'Driscoll, Martin; Skarzynski, Henryk; Skarzynski, Piotr; Usami, Shin-Ichi; Adunka, Oliver; Agrawal, Sumit; Bruce, Iain; et al.
Abstract : Objectives: To provide multidisciplinary cochlear implant teams with a current consensus statement to support hearing preservation cochlear implantation (HPCI) in children, including those children with symptomatic partial deafness (PD) where the intention is to use electric-acoustic stimulation (EAS). The main objectives are to provide guidelines on who is a candidate, how to assess these children and when to implant if Med-El Flex electrode arrays are chosen for implantation. Methods: The HEARRING group reviewed the current evidence and practice regarding the management of children to be considered for HPCI surgery emphasizing the assessment needed prior to implantation in order to demonstrate the benefits in these children over time. The consensus statement addresses following three key questions: (1) Should these children be treated? (2) How to identify these children? (3) How to manage these children? Summary: The HEARRING group concludes that irrespective of the degree of residual hearing present, the concepts of hearing and structure preservation should be applied in every child undergoing cochlear implantation and that HPCI is a safe and reliable treatment option. Early detection and multidisciplinary assessment are key to the identification of children with symptomatic PD, these children should undergo HPCI as early as possible.